Hierarchical status and colour preference in Nile tilapia (Oreochromis niloticus) - Luchiari, Ana Carolina; do Amaral Duarte, Cristiane Regina; de Morais Freire, Fulvio Aurelio; Nissinen, Kari (Springer, 2007)
We studied the colour preference of isolated Nile tilapia (Oreochromis niloticus) and whether previous residence or body size can affect environmental colour choice. In the first phase, a cylindrical tank was divided into five differently coloured compartments (yellow, blue, green, white and red), a single fish was introduced into the tank and the frequency at which this fish visited each compartment was recorded over a 2-day study period. An increasingly larger fish (approx +2 cm in length each time) was then added into the tank on each of days 3, 5 and 7 (=four fish in the tank by day 7), and the frequency at which each fish visited the different compartments of the tank was observed twice a day to obtain visit frequency data on the differently sized fishes. This experiment was replicated six times. In the first phase, the solitary fish established residence inside the yellow compartment on the first and second days. Following the introduction of a larger fish, the smaller fish was displaced from the occupied compartment. Nile tilapia possibly shows this preference for yellow as a function of its visual spectral sensitivity and/or the spectral characteristics of its natural environment. Moreover, body size is an important factor in determining hierarchical dominance and territorial defence, and dominant fish chose the preferred environmental colour compartment as their territory.
Keywords: body size; environmental colour; hierarchy; fish; previous residence